Influence Of Product Quality, Product Design And Promotion On Purchasing Decisions - Fawzia Pratama Putra Herlambang; Rita Tri Yusnita; Ari Arisman (Journal of Indonesian Management, 2022)
This study aims to determine the simultaneous and partial influence of product quality, product design and promotion on purchasing decisions on the Karangnunggal Tasikmalya Fashion Mandate. The research method used in this study is a descriptive method of analysis with a survey approach. The population studied was 100 respondents. The data collected is in the form of secondary and primary data. Data analysis in this study used Multiple Regression Analysis using SPSS software version 26. The results showed that product quality, product design and promotion simultaneously influenced the purchasing decision of Amanah Mode Karangnunggal Tasikmalya. Product quality partially has an insignificant effect on the Purchasing Decision of the Karangnunggal Tasikmalya Fashion Amanah. Product design partially has a significant effect on the Purchasing Decision in the Karangnunggal Tasikmalya Fashion Mandate. The promotion partially had an insignificant effect on the purchasing decision on the Amanah Mode Karangnunggal Tasikmalya.